The big tree - Hiscock, Bruce (New York : Atheneum ; Toronto : Collier Macmillan Canada ; New York : Maxwell Macmillan International Pub. Group, 1991)
Follows the development of a large old maple tree from its growth from a seed during the American Revolution to its maturity in the late twentieth century.
Wilson's Children.
Elem. School Library Collection.
School Library Journal.
5.5
3-6
Keywords: Trees -- Juvenile literature; Trees -- Life cycles -- Juvenile literature; Sugar maple -- Life cycles -- Juvenile literature; Sugar maple -- New York (State) -- Juvenile literature; Trees -- Life cycle; Trees; Trees; Trees -- Life cycles